Effectiveness of the different polishing systems on the surface roughness of composite resins. Bibliographic review - Picón Rentería, Alexa Daniela (2023)
To achieve excellent appearance and durability of composite resins, adequate polishing is required to eliminate surface roughness and obtain an adequate shine. Objective: to carry out a bibliographic review of the effectiveness of the different polishing systems on the surface roughness of composite resins. Methodology: The search was carried out in the databases: Pubmed, Science Direct, Scielo, Cochrane and Google Scholar, selecting 16 publications in English, Portuguese and Spanish since 2017. Results: The bibliographic review yields data that relates fill size of composite resins with the obtaining of surface roughness and gloss, analyzing the difference in results obtained when applying different polishing protocols, from one-step protocols to a complex six-step one. Conclusions: The smaller the particle size of the polishing systems, the better the results in terms of surface roughness and gloss. The systems that present greater complexity are the ones that present the best results. All polishing systems must provide surface roughness values less than or equal to 0.2 µm to ensure aesthetics and health. When applying the polishing systems to nanofilled, nanohybrid, and microhybrid composite restorations, they show similar results.